2012
DOI: 10.1103/physrevlett.108.040503
|View full text |Cite
|
Sign up to set email alerts
|

Indistinguishable Entangled Photons Generated by a Light-Emitting Diode

Abstract: A linear optical quantum computer relies on interference between photonic qubits for logic, and entanglement for near-deterministic operation. Here we measure the interference and entanglement properties of photons emitted by a quantum dot embedded within a light-emitting diode. We show that pairs of simultaneously generated photons are entangled, and indistinguishable from subsequently generated photons. We measure entanglement fidelity of 0.87 and two-photon-interference visibility of 0.60 ± 0.05. The visibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
43
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…In 2013, Gazzano et al showed that good indistinguishability can be achieved in a high brightness source [25]. Stevenson et al [26] showed that a diode structure can produce indistinguishable and entangled photons with electrical pumping. The first to show indistinguishable photons from the biexciton state were Müller et al in 2014 [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Gazzano et al showed that good indistinguishability can be achieved in a high brightness source [25]. Stevenson et al [26] showed that a diode structure can produce indistinguishable and entangled photons with electrical pumping. The first to show indistinguishable photons from the biexciton state were Müller et al in 2014 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of indistinguishable single photons using continuous optical or electrical excitation [22][23][24][25] and pulsed electrical [26,27] excitation has been demonstrated. A relatively high two-photon interference visibility was achieved in electrically driven SPSs [27], despite the system being incoherently pumped and the absence of cavity QED effects in the experiment.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, tremendous progress has been reported in eliminating the fine structure splitting of neutral excitons [16][17][18], improving the extraction efficiency using double-micropillar structures [19] or broadband antennas [20][21][22], and enhancing the entanglement fidelity and photon indistinguishability using resonant excitation [23,24]. Encouragingly, the entanglement fidelity (A) and the photon indistinguishability (D) (for 2 ns separation) has reached 0.978(5) and 0.93 (7), respectively [18,24]. Very recently, the entanglement fidelity of 0.9 (A) was combined with a record-high pair efficiency of 0.37 per pulse, which is the product of the pair generation rate of 0.88 (B) and the extraction efficiency of 0.42 (C), on the same device [22].…”
mentioning
confidence: 99%